Children's Literature and Theology in the Twentieth and Twenty-First Centuries - Blair, Kirstie 1975- (2016)
In 2002, Peter Hunt, one of the world's leading scholars of children's literature, argued in a conference talk: [R]eligion of all kinds has been virtually sile